Pengaruh Pembiayaan Mudharabah Dan Murabahah Terhadap Profitabilitas - Novyanti, Linda Ayu; Wirman, Wirman (Universitas Gorontalo, 2022)
This study aims to determine the effect of Mudharabah, Murabahah simultaneously on profitability (ROE). In this method, the sample used in the population registered at the BRI Syariah bank in 2016 – 2020. The research method uses quantitative methods with statistical data analysis used is the Multiple Linear Regression method. The statistical results show that the mudharabah and murabahah variables partially have no effect on profitability. And simultaneously the mudharabah and murabahah variables have no effect on profitability which is calculated using ROE.